2015
DOI: 10.1007/s11356-015-4240-1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Actinobacteria assemblages in coastal marine sediments under contrasted Human influences in the West Istria Sea, Croatia

Abstract: The exploration of marine Actinobacteria has as major challenge to answer basic questions of microbial ecology that, in turn, will provide useful information to exploit Actinobacteria metabolisms in biotechnological processes. The ecological functions performed by Actinobacteria in marine sediments are still unclear and belongs to the most burning basic questions. The comparison of Actinobacteria communities inhabiting marine sediments that are under the influence of different contamination types will provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 103 publications
2
34
0
Order By: Relevance
“…Analysis based on network will shed light on the mechanisms regulating the interactions among microorganisms that improve AD performance. Recently, there have been several studies in which the potential organization of the microbial community in networks was investigated, such as the microbial community in the soil (Navarrete et al, 2015), marine water (Duran et al, 2015) and human intestine (Zhang et al, 2014). However, little is known about the interactions among microorganisms in AD systems under a temperature gradient, and how these interactions are regulated by temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis based on network will shed light on the mechanisms regulating the interactions among microorganisms that improve AD performance. Recently, there have been several studies in which the potential organization of the microbial community in networks was investigated, such as the microbial community in the soil (Navarrete et al, 2015), marine water (Duran et al, 2015) and human intestine (Zhang et al, 2014). However, little is known about the interactions among microorganisms in AD systems under a temperature gradient, and how these interactions are regulated by temperature.…”
Section: Introductionmentioning
confidence: 99%
“…intI1 to 8 sequences were included (except intI5). IntI libraries were constructed from coastal sediment metagenomes described in Duran et al (2015) and Stauffert et al (2013). Amplification of an 800-bp intI fragment was performed using as primers the inverted complementary sequence of AJH72 (Gillings et al 2005) and intI948R (Elsaied et al 2007).…”
Section: Gene Cassette Diversitymentioning
confidence: 99%
“…4. For more details on samples from Croatia, see Duran et al (2015); on microcosms from French sediments, see Stauffert et al (2013). IntI libraries were obtained as described in Fig.…”
Section: Gene Cassette Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…The powerful resolution of high-throughput sequencing approaches allows the characterization of structural and metabolic changes of microbial communities in contaminated marine ecosystems. The comparison of microbial communities from marine sites with contrasted contamination levels described in Duran et al (2015a) showed specific bacterial assemblages according to the type of contaminant. The study, focusing on Actinobacteria assemblage, revealed the ecological importance of Actinobacteria for maintaining both general biogeochemical functions through a Bcore^Actinobacteria community and specific roles associated with the presence of contaminants.…”
mentioning
confidence: 95%